Using heart rate as a tool to gauge exercise intensity - Bamford, J. (The Journal of Performance Enhancement, 1999)
To achieve optima results, athletes must train at an intensity appropriate to their goals. Intensity is important because too low an intensity will not produce optimal results while too high an intensity can lead to overtraining and injury. In order to maximize training benefits an athlete needs a practical and accurate system to gauge exercise intensity. Heart rate measurement can be used for this purpose. In order to be accurate the athlete must choose a system which directly measures the electrical activity of the heart at the chest. Other methods of monitoring heart rate lack validity. While heart rate is affected by exercise intensity, it is not a direct measurement of it. Heart rate can be affected by other factors such as drug use, hydration status and body position. In order to maximize accuracy, these factors must be controlled.